Circulating markers of angiogenesis and endotheliopathy in COVID‐19. (1st November 2020) - Pine, Alexander B.; Meizlish, Matthew L.; Goshua, George; Chang, C‐Hong; Zhang, Hanming; Bishai, Jason; Bahel, Parveen; Patel, Amisha; Gbyli, Rana; Kwan, Jennifer M.; Won, Christine H.; Price, Christina; et al.
Abstract : Increase in thrombotic and microvascular complications is emerging to be a key feature of patients with critical illness associated with COVID‐19 infection. While endotheliopathy is thought to be a key factor of COVID‐19‐associated coagulopathy, markers indicative of this process that are prognostic of disease severity have not been well‐established in this patient population. Using plasma profiling of patients with COVID‐19, we identified circulating markers that segregated with disease severity: markers of angiogenesis (VEGF‐A, PDGF‐AA and PDGF‐AB/BB) were elevated in hospitalized patients with non‐critical COVID‐19 infection, while markers of endothelial injury (angiopoietin‐2, FLT‐3L, PAI‐1) were elevated in patients with critical COVID‐19 infection. In survival analysis, elevated markers of endothelial injury (angiopoietin‐2, follistatin, PAI‐1) were strongly predictive of in‐hospital mortality. Our findings demonstrate that non‐critical and critical phases of COVID‐19 disease may be driven by distinct mechanisms involving key aspects of endothelial cell function, and identify drivers of COVID‐19 pathogenesis and potential targets for future therapies.